Burden of nursing care: a concept analysis - Vargas-Escobar, Lina María; Aya Roa, Kevin Julián; Ortiz Mayorga, Judith Liliana; Quiñonez Mora, Marcia Andrea; Hernández Bohórquez, Laura Marcela; Fuentes Bermúdez, Genny Paola; Casallas Vega, Alexander (Revista Cuidarte, 2024)
Highlights • From the perspective of the burden of nursing care, patients are holistic beings with multiple components and needs to be met. • The burden of nursing care includes both visible activities, such as direct care, and invisible activities, such as education and care management. • The concept of ’burden of nursing care’ allows the nurse-to-patient ratio to be understood in terms of care needs rather than the number of beds. • The burden of nursing care is the key to assessing the nurse-to-patient ratio in a unit. It identifies needs and levels of dependency and guides nursing activities. Introduction: The burden of nursing care has not been defined as a theoretical or operational concept. However, several studies have demonstrated its impact on the quality of care, the increase in adverse events, and the health of nursing staff. Objective: To analyze the attributes, factors, antecedents, and consequences associated with the concept of ’burden of nursing care’ in order to clarify its meaning. Materials and Methods: A concept analysis was conducted using Walker and Avant’s methodological proposal, which examines a concept’s defining characteristics and attributes. Results: The burden of nursing care is the relation between the needs of patients and the time available for direct care, management, and education activities. Both intrinsic and extrinsic patient factors can influence the patient’s level of dependency and needs, increasing nursing interventions and hours of care, thereby intensifying the burden of care. Discussion: The burden of nursing care involves patient-centered care with adequate resources. The burden of nursing care demands planning and leadership from nurses. A lack of competencies and experience, combined with institutional inflexibility, increases the burden of nursing care, leading to dissatisfaction and adverse events. Conclusions: The burden of nursing care is a concept that is epistemically grounded in the interactive-integrative view because it focuses on meeting patients’ needs through nursing interventions for direct care, management, and education. How to cite this article: Vargas-Escobar Lina María, Aya Roa Kevin Julián, Ortiz Mayorga Judith Liliana, Quiñonez Mora Marcia Andrea, Hernández Bohórquez Laura Marcela, Fuentes Bermúdez Genny Paola, Casallas Vega Alexander. Burden of nursing care: a concept analysis. Revista Cuidarte. 2024;15(3):e3848. https://doi.org/10.15649/cuidarte.3848